2018
DOI: 10.1017/s1355617718000425
|View full text |Cite|
|
Sign up to set email alerts
|

Change in Cognitive Performance From Midlife Into Old Age: Findings from the Midlife in the United States (MIDUS) Study

Abstract: Objective A substantial body of research has documented age-related declines in cognitive abilities among adults over 60, yet there is much less known about changes in cognitive abilities during midlife. The goal was to examine longitudinal changes in multiple cognitive domains from early midlife through old age in a large national sample, the Midlife in the United States (MIDUS) study. Method The Brief Test of Adult Cognition by Telephone (BTACT) was administered on two occasions (MIDUS 2, MIDUS 3), an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 100 publications
(123 reference statements)
10
134
1
2
Order By: Relevance
“…Longitudinal studies that address sex differences in older humans generally indicate poorer episodic memory in men. There is a debate concerning sex differences in the trajectory of cognitive impairments, with results indicating no difference or a steeper decline in males (Finkel et al, 2003;Ferreira et al, 2014;Lundervold et al, 2014;McCarrey et al, 2016;Olaya et al, 2017;Hughes et al, 2018;Lee et al, 2018;Casaletto et al, 2019). Cross-sectional rodent studies indicate age and sex differences in tasks that involve repeated acquisition of spatial information and episodic memory (Lukoyanov et al, 1999;Markowska, 1999;Rossetti et al, 2018); nevertheless, most longitudinal studies in animal models of aging have not compared sex differences in the decline of memory.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies that address sex differences in older humans generally indicate poorer episodic memory in men. There is a debate concerning sex differences in the trajectory of cognitive impairments, with results indicating no difference or a steeper decline in males (Finkel et al, 2003;Ferreira et al, 2014;Lundervold et al, 2014;McCarrey et al, 2016;Olaya et al, 2017;Hughes et al, 2018;Lee et al, 2018;Casaletto et al, 2019). Cross-sectional rodent studies indicate age and sex differences in tasks that involve repeated acquisition of spatial information and episodic memory (Lukoyanov et al, 1999;Markowska, 1999;Rossetti et al, 2018); nevertheless, most longitudinal studies in animal models of aging have not compared sex differences in the decline of memory.…”
Section: Introductionmentioning
confidence: 99%
“…Several precautions were taken to ensure our samples of middle-aged and older adults who retired versus remained employed were directly comparable. This was accomplished by (a) selecting individuals who were working at baseline and who either retired or remained employed nine years later and (b) using propensity score matching to equate participants on central demographic and health variables linked to cognitive functioning: age, gender, education, income, occupation, and health status (Hughes et al, 2018;Lachman et al, 2014;. We adopted propensity score matching over alternative procedures because this approach has been shown to improve balance on influential covariates and thereby reduce bias in parameter estimates of sample differences (Austin, 2011;West et al, 2014).…”
Section: Comparability Of Retirees and Employeesmentioning
confidence: 99%
“…Empirically, past studies have shown that episodic memory and executive functioning typically ONLINE SUPPLEMENTAL MATERIALS 4 begin to decline more rapidly in midlife after age 50 (Hughes et al, 2018;Lachman et al, 2014).…”
Section: Rationale For Age Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, content-context binding (Cowan et al, 2006;Hommel, Kray & Lindenberger, 2011;Siegel, 1994;Swanson, 2017) and switch (Kray, Eber & Lindenberger, 2004;Reimers & Maylor, 2005) decrease approximately linearly across the adult life-span. The decline of memory, process speed, inhibition and reasoning begin from middle age (Anstey et al, 2015;Borella, Carretti & De Beni, 2008;Davis et al, 2017;Hughes et al, 2018;Persad et al, 2002;Singh-Manoux et al, 2012;Zimprich & Mascherek, 2010). Although the timing of age-related decline of cognitive functions varies, middle age looks like an important age boundary.…”
Section: Introductionmentioning
confidence: 99%